The Polish court banner in the Moldavian expedition in 1497 - Tadeusz Grabarczyk (Fasciculi Archaeologiae Historicae, 2017)
The paper discusses the expedition of the Kingdom of Poland to Moldavia in 1497. The army of 50,000 included a detachment of courtiers (curienses) who were organised as the so-called court banner. It was a kind of royal guard of up to 2000 men. The army, led by the Polish king John I Albert, set off at the beginning of June from Lviv, and on 24 September the troops began a siege of Suceava, the capital of Moldavia. A well-fortified city was not captured and on 19 October the siege ended. During the retreat, on 26 October the Polish troops were attacked by the Moldavians and their allies in the Cosmin Forest in Bucovina (present-day Ukraine). In the clash, the court banner played an important role, by saving the knights of the general levy from a complete defeat. In the Central Archives of Historical Records in Warsaw there are registers of armaments lost in this battle by the curienses. The paper discusses the armaments of members of the court detachment and losses they suffered during the battle.